Effect of combination antiretroviral therapy on the frequency of oral candidiasis in HIV/AIDS patient - Sayuti Hasibuan (Dental Journal (Majalah Kedokteran Gigi), 2007)
Oral candidiasis is one of the most common opportunistic infections in HIV/AIDS patients. It serves as important markers of HIV infection, viral load, and CD4 cells count in the blood and predict disease progression to AIDS. The development of oral candidiasis in HIV/AIDS patients associated by imbalances between Candida and impaired host immune defenses that caused by decreased of CD4 cell counts and the increased of plasma HIV-viral load. Since the introduction of antiretroviral therapy combination, commonly known as Highly Active Antiretroviral Therapy (HAART), it has been observed that certain oral lesions, such as oral candidiasis as declined. The aim of this paper is to review the mechanism of combination antiretroviral therapy influenced the frequency of oral candidiasis in HIV/AIDS patient. We conclude that combination antiretroviral therapy generally reduced the frequency and severity of oral candidiasis in HIV/AIDS patient.